Separation of Source-Network Coding and Channel Coding in Wireline Networks - Jalali, Shirin; Effros, Michelle (IEEE transactions on information theory, 2015)
In this paper, we prove the separation of source-network coding and channel coding in wireline networks. For the purposes of this paper, a wireline network is any network of independent, memoryless, point-to-point, and finite-alphabet channels used to transmit dependent sources either losslessly or subject to a distortion constraint. In deriving this result, we also prove that in a general memoryless network with dependent sources, lossless, and zero-distortion reconstruction are equivalent provided that the conditional entropy of each source given the other sources is nonzero. Furthermore, we extend the separation result to the case of continuous-alphabet and point-to-point channels, such as additive white Gaussian noise channels.